(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Starch nanoparticles (StNPs) have attracted growing attention due to their unique properties as a sustainable alternative to common nanomaterials since they are natural, renewable and biodegradable. The present study reports green synthesized StNPs using the old Asparagus racemosus plant. UV-Vis spectroscopy, FT-IR and AFM analysis revealed that synthesized StNPswith an average particle size of 6.25μm. Comparatively, the ethanol extracts showed that MIC and MBC against Staphylococcus aureus. Starch and aqueous extracts showed antibiofilm activity against S.aures, lactobacillus sp., and E.coli 25μg/ml. The preliminary screening showed that the A.racemosus extracts of aqueous and ethanol extracts have various reducing phytochemicals, including alkaloids, flavonoids, and saponins. StNPs have been used to encapsulate bioactive compounds for controlled release in biomedical applications such as drug administration, enzyme inhibition process, and DNA precipitation